An explanatory study on the adoption of IFRSs for SMEs in Zimbabwe’s SME sector - Dlamini, Banele; Gumede, Phathisani (The Journal of Accounting and Management, 2025)
This paper explored the level of adoption of International Financial Reporting Standards (IFRS) for Small and Medium Enterprises (SMEs) by SMEs in Zimbabwe. The study identified the motivations for SMEs to adopt IFRS for SMEs and uncovered the challenges SMEs face during the adoption process. The study employed an explanatory research design within the pragmatism paradigm. A mixed-methods research approach was adopted, and quantitative data was collected using a five-point Likert scale and semi-structured interviews. The study found a low adoption level of IFRSs for SMEs in the SME sector in Zimbabwe. SMEs were motivated to adopt IFRSs by aligning with IFRS, enhancing stakeholders' credibility, and improving financial reporting and transparency. The study discovered that the major reasons for the non-adoption of IFRSs for SMEs were attributed to a lack of awareness about IFRSs for SMEs, the complexity of IFRS implementation, cost consideration, a lack of knowledge and expertise in the implementation of IFRSs, and limited resources for training. The results also revealed that difficulties in understanding and interpreting IFRS requirements, limited support from the regulatory board, lack of resources in implementing IFRS, availability of skilled professionals in IFRS compliance, and resource constraints in implementing were the major challenges faced by SMEs in the adoption and implementation of IFRS for SMEs. The study recommended that SMEs adopt IFRSs for SMEs to produce high-quality financial statements that enable effective economic decision-making. It is recommended that the regulatory board implement targeted awareness campaigns and educational programmes to increase awareness and understanding of the benefits of adopting IFRSs among SMEs in Zimbabwe